Advances in Endovascular Intervention Using Biomaterials: Study on Heat Efficiency of Scissor-Type Ultrasonic Catheter Device. (10th March 2021) - Morita, Minoru; Yang, Jingjing; Jiang, Zhongwei
Abstract : To improve the performance of the ultrasonic device during the endovascular operation, a scissor-type ultrasonic catheter device with compound vibration was developed. The heat generated by friction between the target and the device affects its coagulation mechanism while the actuator contacts the tissue. The scissor-type ultrasonic catheter device proposed in this study is expected to improve heat generation performance because it has the action of rubbing the object when it is pushed by combined vibration. In addition, since it is constructed by simple notch processing, it can be miniaturized and can be expected to be introduced into catheters. However, the observation of ultrasonic vibration during frictional heating is difficult, which is an issue for device design. In this paper, a thermal-structure coupling analysis was done using the finite element method to calculate the heat generation efficiency and evaluate its coagulation performance.